Efektivitas Bahan Alami Sebagai Agen Antimikroba dalam Pengobatan Penyakit Ikan Air Tawar: Tinjauan Literatur - Destriman Laoli; Nelvia Mai Susanti; Rahmat Tillah; Betzy Victor Telaumbanua; Ratna Dewi Zebua; Januari Dawolo; Okniel Zebua; Asokhiwa Zega (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
This study evaluates the effectiveness of natural materials as antimicrobial agents in the treatment of freshwater fish diseases, with the aim of offering a safer and more sustainable alternative to synthetic chemicals and antibiotics. Using the literature review method, this study analyzed relevant current scientific articles. Results showed that extracts of betel leaf, neem leaf, cinnamon essential oil, basil essential oil, aloe vera, and propolis had significant antimicrobial activity against freshwater fish pathogens such as Flavobacterium columnare and Aeromonas hydrophila. Betel leaf extract and cinnamon essential oil showed inhibition rates of up to 85% and 82%, respectively. The advantages of using natural ingredients include environmental safety, reduced risk of antimicrobial resistance, and immunostimulating effects in fish. However, challenges such as ingredient availability, cost, and standardization still need to be addressed. This study suggests the development of natural ingredient-based products, standardization and quality testing, further research, and training for fish farmers. Collaboration between stakeholders is also important to reduce dependence on antibiotics. In conclusion, natural ingredients have great potential as effective and environmentally friendly antimicrobial agents in freshwater fish health management.